Tài liệu hướng dẫn xây dựng và quản lý hệ thống nông lâm kết hợp cho cà phê - Vaast, Philippe; Rachmat, Mulia; Nguyen Mai Phuong; Duong Minh Tuan; Tran Ha My; Nguyen Thi Van; Vu Hong Trang; Nguyen Minh Phuong; Hoang Quoc Viet (2020)
This document is used as a handout for farmers participating in a series of training on coffee-based agroforestry management practices.